MEMINIMALISIR KECENDERUNGAN KECURANGAN AKUNTANSI PADA SISTEM PENGENDALIAN INTERNAL - Nurul Anisa; Windi Istiqomah; Eka Tertiana (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2021)
Abstract To minimize dishonesty, it is necessary to have Internal Operations which play a very important role in an organization. Effective internal operations will cover the possibility of fraud in accounting. The internal operating tools help lay the auditor's confidence about his / her financial statements from possible fraud and errors. In order for the Institution to improve the internal operating structure, implement and monitor it so that the company can be realized, good internal operations will ensure the accuracy of the resulting accounting data so that the data cannot be trusted. The purpose of this study is to analyze fraud in financial reporting. This research was conducted using a qualitative descriptive method. Data taken from research PT. Taspen (Persero) Tanjungpinang. The results showed that the operating environment, risk determination, operating activities, accounting information and communication systems, and individually (partially) or collectively (simultaneously) played quite a role in anticipating the trend of accounting insincerity. The author reports that internal control is very important in terms of management, supervision and company procedures. The author also provides suggestions for each company to control the internal system and evaluate the work performed by the company's internal auditors.